Evaluation On Self-Adjusted Phosphate Binder Administration To Dietary Phosphate Contents In Management Of Hyperphosphatemia Among Hemodialysis Patients In Penang, Malaysia - Khor, Su Mee (2018)
Hyperphosphatemia is a serious problem that is associated with high mortality rate among the dialysis patient. Many studies have revealed that the dialysis and dietary restriction are insufficient for managing hyperphosphatemia. Thus, phosphate binder is usually required for the dialysis patients. Current diet counseling on low phosphate diet did not effectively lower the phosphate level. Therefore, this study was designed to evaluate the effectiveness of a newly intervention booklet that contains 80 common eaten foods that allowed the Penang hemodialysis patients to self-adjusted phosphate binder administration to their dietary phosphate content.